ANALISIS PENDAPATAN DAN NILAI TAMBAH AGROINDUSTRI TAPE SINGKONG DI KOTA PEKANBARU - Ari Nurhayati Praptiwi; Ermi Tety; Jumatri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objectives of this study were: 1) to determine the amount of costs, revenues, profits, and profitability value of tapai agroindustry in Pekanbaru. 2) to determine the level of efficiency of cassava tapai agroindustry in Pekanbaru. 3) to determine the added value of cassava tapai agroindustry in Pekanbaru. This research was conducted from January 2014 unti Mei 2014. The data collection technique was cencus technique. The respondents of this research were all active to tapai entrepreneurs in Pekanbaru. This research used qualitative and quantitative methods. The analysis scopes of this research were costs, revenues, profits, profitability, efficiency, and added values analysis. The results of this research showed that the average total cost of tapai agroindustry in Pekanbaru was Rp. 11.786.066,66 per month. . Total revenues of tapai agroindustry in Pekanbaru was Rp.18.116.343,99 per month. Total Profit of tape agroindustry in Pekanbaru was Rp. 6.330.277,33 per month. The number 53,71 percent of Profitability value meant that tapai agroindustry in Pekanbaru was a profitable industry because the value of profitability > 1,53 Ratio of R / C value meant that every Rp.1.00 costs in the production process of tape will provide 1,53 times profit. The average added value of tapai was Rp.5.666,67/kg. Keywords: Tapai, Agroindustry, Efficiency, Value Added